The Dual Role of Women and Digital Literacy in Improving the Performance of the Home and Industrial Social Center of the Fisherwomen's Group: JEL Classification: J16, O33, D83, J22, L26 - Imaduddin Imaduddin; Muh. Haerdiansyah Syahnur; Amirullah Amirullah; Andi Zulfikar Syaiful; Haerani Haerani (Journal La Bisecoman, 2025)
This paper explores how fisherwomen in Makassar mediate the compounded tensions of family obligation and economic labor of co-operation as they adjust to digital technologies in the Home and Industrial Social Center. With a qualitative descriptive design, which is supported by phenomenology and has a linkage-bridging viewpoint, the study looks at how digital literacy is transforming quotidian practices, moderating collaborative practice, and intertwining with culturally normative values that command shared practice. Fifteen participants were interviewed using in-depth interviews and participant observation and reviewed documents, which allowed gathering data related to the pragmatic experience, as well as the emotional and embodied aspects of digital engagement. The results suggest that the digital literacy is a transformative force that broadens the market, enhances the efficiency of the operations, and strengthens the feeling of agency in the fisherwomen. At the same time, it is associated with new stressors, such as physiological exhaustion, time disruption, and increased domestic tension levels in regard to prolonged online activity. Instead of reducing the dual burden, the digital tools re-structure it into a hybrid taxonomy of domestic, manual and digital work which the women have to negotiate all the time. The analysis of linkage-bridging shows that internal resources (siri Naa pacce and peer-based learning) are compatible with external digital resources to enable adaptive capabilities within the cooperative. This overlap brings about the Dual Digital Bridge framework which illustrates how local cultural values can be made in line with technological innovation in coastal locations.